Knowledge, attitudes and practices related to schistosomiasis transmission and control in Leyte, Philippines. - Isabel Francisco; Mario Jiz; Marieke Rosenbaum; Palmera Baltazar; Jennifer A Steele (Public Library of Science (PLoS), 2019)
Schistosomiasis is a chronic but preventable disease that affects 260 million people worldwide. In the Philippines, 860,000 people are afflicted with Schistosoma japonicum annually, and another 6.7 million live in endemic areas. The disease's complex epidemiology as well as the influence of poverty in endemic areas demand an integrated, multi-sectoral approach to disease control. Results from behavioral or sociocultural studies on schistosomiasis could improve the content and impact of schistosomiasis control in rural villages in the Philippines. We investigated knowledge, attitudes and practices related to schistosomiasis transmission and control in an endemic village in Leyte Province, Philippines. We administered a questionnaire to 219 participants covering 1) knowledge and attitudes related to schistosomiasis, its symptoms, and its transmission; 2) attitudes and practices in relation to schistosomiasis prevention; 3) willingness to comply with public health control programs; and 4) whether the respondent had previously contracted schistosomiasis. Responses revealed fairly high measures of schistosomiasis knowledge (mean 17.0 out of 23 questions, range 6-23), but also inconsistent disease prevention behavior. A high proportion of participants (72.6%, n = 159) reported previous disease. Participant belief in the preventability of schistosomiasis was revealed to be a key attitude, as carabao owners who believed in prevention were over five times more likely to be willing to vaccinate their carabaos (OR = 5.24, 95% CI 1.20-27.68, P = 0.04). Additionally, participants who did not believe in prevention were about twice as likely to report previous disease (OR = 2.31, 95% CI 1.02-5.63, P = 0.05). Our results suggest that future public health interventions should address barriers to disease-preventing behavior, as well as maintaining community belief in disease prevention. Comprehensive disease control programs should be supplemented by sociocultural and behavioral context in order to improve their impact in endemic communities.